Green Accounting and Profitability: Evidence from PROPER Mining Firms in Indonesia - Kareen Andina; Violetta Elsa Namira Susanto; Haryanto Haryanto (Jurnal Eksplorasi Akuntansi, 2026)
Sustainability has become a strategic issue for mining companies because their operations create direct environmental and financial consequences. This research examines the effect of environmental costs, green investment, and environmental disclosure on the profitability of PROPER-participating mining companies listed on the Indonesia Stock Exchange during 2022–2024. Profitability is measured using return on assets. The study uses a quantitative associative approach based on secondary data from annual reports, sustainability reports, and PROPER publications. The final sample comprises 13 mining companies and 39 firm-year observations. Panel data regression is applied, and the model specification tests indicate that the Random Effects Model is the most appropriate. The results show that environmental costs have a significant negative effect on profitability, whereas green investment and environmental disclosure have no significant effect. These findings indicate that green accounting practices do not automatically improve short-term profitability in the mining sector. Environmental costs may still pose a financial burden when immediate expenditures outweigh short-term benefits. Green investment and environmental disclosure may require longer time horizons and stronger operational integration before their financial effects appear in ROA. This study contributes to green accounting literature by showing that environmental costs, investment, and disclosure have distinct financial implications.